Benzolactam-related compounds promote apoptosis of HIV-infected human cells via protein kinase C–induced HIV latency reversal - Matsuda, Kouki; Kobayakawa, Takuya; Tsuchiya, Kiyoto; Hattori, Shin-ichiro; Nomura, Wataru; Gatanaga, Hiroyuki; Yoshimura, Kazuhisa; Oka, Shinichi; Endo, Yasuyuki; Tamamura, Hirokazu; Mitsuya, Hiroaki; Maeda, Kenji (The Journal of biological chemistry, 2019)
Latency-reversing agents (LRAs) are considered a potential strategy for curing cells of HIV-1 infection. Certain protein kinase C (PKC) activators have been previously reported to be LRAs because they can reverse HIV latency. In the present study, we examined the activities of a panel of benzolactam derivatives against cells latently infected with HIV. Using determination of p24 antigen in cell supernatants or altered intracellular GFP expression to measure HIV reactivation from latently infected cells along with a cytotoxicity assay, we found that some of the compounds exhibited latency-reversing activity, which was followed by enhanced release of HIV particles from the cells. One derivative, BL-V8-310, displayed activity in ACH-2 and J-Lat cells latently infected with HIV at a concentration of 10 nm or higher, which was superior to the activity of another highly active PKC activator, prostratin. These results were confirmed with peripheral blood cells from HIV-infected patients. We also found that these drugs up-regulate the expression of caspase 3 and enhance apoptosis specifically in latently HIV-infected cells. Moreover, combining BL-V8-310 with a bromodomain-containing 4 (BRD4) inhibitor, JQ1, not only enhanced HIV latency-reversing activity, but also reduced the effect on cytotoxic cytokine secretion from CD4+ T-cells induced by BL-V8-310 alone. Our results suggest that BL-V8-310 and its related benzolactam derivatives are potential LRA lead compounds that are effective in reversing HIV latency and reducing viral reservoirs in HIV-positive individuals with few adverse effects.